2021
DOI: 10.3389/fonc.2021.746789
|View full text |Cite
|
Sign up to set email alerts
|

m6A Modification in Non-Coding RNA: The Role in Cancer Drug Resistance

Abstract: Cancer drug resistance has always been a major difficulty in cancer therapy. In the face of drug pressure, resistant cancer cells show complex molecular mechanisms including epigenetic changes to maintain survival. Studies prove that cancer cells exhibit abnormal m6A modification after acquiring drug resistance. m6A modification in the target RNA including non-coding RNA can be a controller to determine the fate and metabolism of RNA by regulating their stability, subcellular localization, or translation. In p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 156 publications
(214 reference statements)
1
5
0
Order By: Relevance
“…However, data from the TCGA database show that YTHDF3 is downregulated in CRC patients. , Nonetheless, our study mainly focused on OXAR CRC cell lines and tissues, which we suspect are different from patient-derived CRC tissues. Moreover, our results indicate that YTHDF3 binds to the 5′ UTR to control gene translation (Figure C), which is consistent with a previous study, showing that YTHDF3 induces gene translation of transcripts that are m6A-enriched at the 5′ UTR, , and YTHDF3 per se does not affect m6A methylation but may determine RNA fate and metabolism . Although it has been previously demonstrated that YTHDF3 is implicated in drug resistance and metastasis in lung cancer, , the molecular role of YTHDF3 in modulating gene translation in platinum resistance remains poorly understood.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, data from the TCGA database show that YTHDF3 is downregulated in CRC patients. , Nonetheless, our study mainly focused on OXAR CRC cell lines and tissues, which we suspect are different from patient-derived CRC tissues. Moreover, our results indicate that YTHDF3 binds to the 5′ UTR to control gene translation (Figure C), which is consistent with a previous study, showing that YTHDF3 induces gene translation of transcripts that are m6A-enriched at the 5′ UTR, , and YTHDF3 per se does not affect m6A methylation but may determine RNA fate and metabolism . Although it has been previously demonstrated that YTHDF3 is implicated in drug resistance and metastasis in lung cancer, , the molecular role of YTHDF3 in modulating gene translation in platinum resistance remains poorly understood.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, our results indicate that YTHDF3 binds to the 5′ UTR to control gene translation (Figure 3C), which is consistent with a previous study, showing that YTHDF3 induces gene translation of transcripts that are m6A-enriched at the 5′ UTR, 26,27 and YTHDF3 per se does not affect m6A methylation but may determine RNA fate and metabolism. 28 Although it has been previously demonstrated that YTHDF3 is implicated in drug resistance and metastasis in lung cancer, 13,14 the molecular role of YTHDF3 in modulating gene translation in platinum resistance remains poorly understood. The second important observation of our study is the synergistic effect of YTHDF3 with translation initiation factors in OXAR CRC cells, which is different from that in non-resistant cancer cells.…”
Section: ■ Discussionmentioning
confidence: 99%
“…A growing number of studies have shown that m6A methylation serve as a potential biomarker for therapy resistant cancer cells [ 90 92 ]. Methods of determining the m6A methylation includes LC-MS/MS, Colorimetric and MeRIP-seq.…”
Section: Methods Of Determining the M6a Methylationmentioning
confidence: 99%
“…N6-methyladenosine (m6A) methylation modifications are the most frequent internal RNA modifications in eukaryotes ( 12 ). A growing number of findings suggest that noncoding RNA level may be associated with m6A methylation modifications ( 13 ). For example, researchers have found that lncRNA XIST can form the RBM15/RBM15B-WTAP-METTL3 complex to regulate transcriptional silencing of genes, which recruits the silencing complex ( 14 ).…”
Section: Introductionmentioning
confidence: 99%